Synthesis and Characterization of Biodegradable Blend based on LDPE/cassava stem nanofiber cellulose - Lismeri, L; Herdiana, N; Kameswara, D; Darni, Y; Azhar, Azhar (Journal of Chemical Process Engineering, 2021)
Conventional plastics becomes trend topic due to its long degradation time and needs attention related to environmental problem. One type of plastic that is difficult to be degraded is LDPE. Some of the efforts were done to synthesize biodegradable plastic based on organic material to accelerate the degradation process. Cellulose is an organic material that is abundant in nature and can be used as filler. This research aims to synthesis the biodegradable plastic films composted by the nanocellulose cassava stems and recycled LDPE. Mechanical (UTM), water resistance and degradation test has been done. The properties of the biodegradable composites still meet the commercial LDPE. Even though the biocomposite based on LDPE-nanofiber cellulose do not degradable totally but it is can be used as a solution to reduce the degradation time of a plastic waste.